Molecular genetics of arsenic resistance of the biomining bacterium Acidithiobacillus ferrooxidans - Butcher, Bronwyn Gwyneth (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--Stellenbosch University, 2003.